The Moderating Role of Audit Quality in the Relationship between Good Corporate Governance and Leverage on Financial Statement Integrity - Assobary, Alfanna Ibnu; Yudi, Yudi; Ridwan, Muhammad (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: he integrity of financial statements is essential for maintaining investor and creditor confidence, particularly in capital-intensive sectors such as infrastructure. Background Problems: Recurrent financial reporting scandals in Indonesia, including cases involving major state-owned enterprises, indicate weaknesses in corporate governance and external audit effectiveness. High leverage further intensifies financial pressure, potentially encouraging earnings manipulation. Prior studies on the relationship between Good Corporate Governance (GCG), leverage, audit quality, and financial statement integrity show inconsistent results. Novelty (optional): This study introduces audit quality as a moderating variable in the relationship between GCG and leverage on financial statement integrity, specifically within infrastructure companies listed on the Indonesia Stock Exchange during 2022–2024. Research Methods: A quantitative explanatory approach was employed using secondary data from 41 companies (123 observations). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Finding/Results: The results reveal that GCG, leverage, and audit quality do not have a significant direct effect on financial statement integrity. Additionally, audit quality does not moderate the relationship between GCG and financial statement integrity. However, audit quality significantly moderates the relationship between leverage and financial statement integrity, indicating its role in mitigating risks associated with high debt levels. Conclusion: The findings suggest that internal governance mechanisms alone are insufficient to ensure financial reporting integrity. Audit quality plays a crucial role, particularly in high-leverage conditions, although the overall explanatory power of the model remains limited.